Libraries and Censorship : The Accessibility to Information in Wisconsin Public Library Systems - Alt, Annalyn; Anderson-Lind, Seth; Fritz, Derek; Kassner, Austin; Knapp, Karin; McCarty, Clare; Smith, Hillary; Wacholz, Blake; Kaldjian, Paul J. (My University, 2017)
Public libraries are centers for accessing ideas and information, some of which is perceived as controversial by members of their communities. As such, libraries often receive challenges from community members over books they feel are inappropriate, especially for children’s and young adult books. As protectors of public access to ideas and information, libraries take their responses to book challenges very seriously. Removing books from the collection would be censorship; however, anticipating and avoiding conflict by not obtaining a controversial book could be an act of self-censorship. This research examines the relationship between challenged books and Wisconsin public libraries. Since 1990, the American Library Association (ALA) has kept track of books that have been challenged. In this project, we have looked at the availability of 20 commonly and recently challenged books with diverse content across all county libraries in Wisconsin; we mapped this information to better understand the geography of access to information and ideas. We are looking for regional patterns in the availability of books with diverse content in Wisconsin public libraries, and what a varied access to such content may suggest about the state.
Color poster with text, maps, and figures.
Keywords: Censorship; Public libraries; Posters